RESEARCH STUDIES IN SECOND LANGUAGE WRITING AND IN CONTRASTIVE RHETORIC - Cahyono, Bambang Yudi (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
The major aim of this article is to review studies of second language writing. The first part deals mainly with the process of writing in the second and first languages. The second part concerns contrastive rhetoric. In this second part, the findings of research studies on the relationship of first and second language rhetoric will be presented. Included in the discussion are research studies on contrastive rhetoric in the Indonesian context. The last section of this article concludes the discussion and proposes the implementation of more research on the relationship between Indonesian rhetoric and English rhetoric in essays written by Indonesian learners of English.